Integration of Knowledge, Attitude, And Preparedness of Health Workers in Facing Flood Disaster - Agustina Boru Gultom (ACHSM, 2023)
The quality of health services in flood disaster conditions still needs to get better attention because health workers carry out actions in this condition that are not yet effective. It was closely related to the quality of preparedness of these health workers. The quality can reflect whether there was an integration of health workers' knowledge, attitude, and preparedness in dealing with flood disasters. The study used a mixed method consisting of a quantitative design with a correlation test and a qualitative design with interviews. The study with a quantitative design used a total population of 22 health workers, and a qualitative design uses 8 participants who are representatives of each profession. Analysis used univariate analysis and bivariate analysis with Fisher's exact test. Knowledge and preparedness of health workers to face flood disasters were still not good and not ready when compared to attitudes. Knowledge relates to preparing the health workers to face flood disasters with p 0,009, and a study with a qualitative design using 8 participants who are representatives of each profession. Health workers dealing with flood disasters have not fully integrated knowledge, attitudes, and preparedness. We need to improve aspects of behavior that are still not optimal.